Reliability and safety of elevators and escalators/ travelators: Past, present and future - Ping Kwan Man; Chak-Nam Wong; Wai Kit Chan; Hiu Hung Lee; Jingyuan Huang; Michael Pecht (Results in Engineering)
Elevators, escalators and travelators have been developed to enable people to save time and physical strength when traveling. As places such as shopping malls, hotels and airports have become dependent on these transportation technologies, major problems can occur when they stop working. This paper reviews the historical steps used to address the reliability and safety of these human transportations – technologies and how fault diagnosis, fault detection and health monitoring, and maintenance forecasting are now being implemented, as well as the potential for further advancements.